Factors Influencing Music Career Choice Among Malaysian Students: A Social Cognitive Career Theory Perspective - Shamsul Amri Abdul Manap; Adil Johan; Mohd. Sobhi Ishak (Malaysian Journal of Music, 2025)
Careers in music have begun to gain attention within the Malaysian community. With formal music education available from primary to tertiary levels, students are increasingly likely to pursue music careers, a process that involves a series of cognitive and behavioural changes. Using Social Cognitive Career Theory (SCCT) as a basis, semi-structured interviews were conducted in this study to identify cognitive, contextual, and affective attributes that influence music career choices in Malaysia. Thematic and socio-cultural analyses, supported by NVivo software, revealed several key factors: enthusiasm (cognitive), parental and environmental support (contextual), and spirituality (affective). These attributes are seen to greatly influence the tendency towards choosing a music career in the Malaysian context.